2017
DOI: 10.1021/acs.chemrev.7b00291
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Inspired Structural Materials for Flexible Electronic Devices

Abstract: Exciting advancements have been made in the field of flexible electronic devices in the last two decades and will certainly lead to a revolution in peoples' lives in the future. However, because of the poor sustainability of the active materials in complex stress environments, new requirements have been adopted for the construction of flexible devices. Thus, hierarchical architectures in natural materials, which have developed various environment-adapted structures and materials through natural selection, can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
409
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 655 publications
(409 citation statements)
references
References 736 publications
(1,531 reference statements)
0
409
0
Order By: Relevance
“…

result, a series of helpful tools or apparatuses (like hacksaw-mantis, radar-bat, and gyrotron-fly) have been invented. [24][25][26][27][28] In addition, besides high-performance active materials, a flexible, porous, and self-supporting substrate is also crucial for developing a freestanding electrode without conductive or adhesive agents. [2,[4][5][6][7][8][9] For instance, directional water collection material, [10] antireflection film, [11,12] and superhydrophobic surface [13] have been designed and prepared by mimicking the microstructures of spider silk, transparent wings of glasswing butterfly/moth eye, and lotus leaf, respectively.

In the field of electrochemical energy storage, natural structures (like bamboo, [14] flower, [15,16] forest, [17,18] and honeycomb [19,20] ) have been and continue to be intriguing as models for molding similar micromorphologies of electrochemically active materials since these multiscale hierarchical structures exert enormous functions on electrochemical reactions (e.g., increasing reaction area, [21] providing fast electron paths, [22] and reducing diffusion path of electrolyte ions [23] ).

…”
mentioning
confidence: 99%
“…

result, a series of helpful tools or apparatuses (like hacksaw-mantis, radar-bat, and gyrotron-fly) have been invented. [24][25][26][27][28] In addition, besides high-performance active materials, a flexible, porous, and self-supporting substrate is also crucial for developing a freestanding electrode without conductive or adhesive agents. [2,[4][5][6][7][8][9] For instance, directional water collection material, [10] antireflection film, [11,12] and superhydrophobic surface [13] have been designed and prepared by mimicking the microstructures of spider silk, transparent wings of glasswing butterfly/moth eye, and lotus leaf, respectively.

In the field of electrochemical energy storage, natural structures (like bamboo, [14] flower, [15,16] forest, [17,18] and honeycomb [19,20] ) have been and continue to be intriguing as models for molding similar micromorphologies of electrochemically active materials since these multiscale hierarchical structures exert enormous functions on electrochemical reactions (e.g., increasing reaction area, [21] providing fast electron paths, [22] and reducing diffusion path of electrolyte ions [23] ).

…”
mentioning
confidence: 99%
“…[7] In these MOFs,t he swelling can be strongly influenced by the solvent and by the functional groups in the linkers. [13] Fori nstance,p lant tissues have developed diverse mechanisms for reversible and efficient shape transformations,w hich are typically driven by ambient humidity variations. [8b] Our group considered that the aforementioned phenomenon had been overlooked in the development of functional materials,sowebegan to reflect on how such swelling might be exploited to develop novel soft materials capable of reversible shape transformations.I nt his regard, self-folding materials,which are able to translate external stimuli such as thermal, light, electrical, or chemical energy into useful and predictable shape transformations,are garnering attention for their potential utility in applications such as robotics, [9] artificial muscles, [10] energy harvesting, [11] and encapsulation.…”
mentioning
confidence: 99%
“…[8b] Our group considered that the aforementioned phenomenon had been overlooked in the development of functional materials,sowebegan to reflect on how such swelling might be exploited to develop novel soft materials capable of reversible shape transformations.I nt his regard, self-folding materials,which are able to translate external stimuli such as thermal, light, electrical, or chemical energy into useful and predictable shape transformations,are garnering attention for their potential utility in applications such as robotics, [9] artificial muscles, [10] energy harvesting, [11] and encapsulation. [13] Fori nstance,p lant tissues have developed diverse mechanisms for reversible and efficient shape transformations,w hich are typically driven by ambient humidity variations. [13] Fori nstance,p lant tissues have developed diverse mechanisms for reversible and efficient shape transformations,w hich are typically driven by ambient humidity variations.…”
mentioning
confidence: 99%
“…Generally, soft elastomer and conductive materials are indispensable components to build a highly sensitive tactile sensor . It is also found that structural design is critical to determine the sensitivity of tactile sensors . With micro/nanostructured elastomers or conductors, the tactile sensors can possess very high sensitivities and other functions.…”
Section: Introductionmentioning
confidence: 99%